The Chilean school under the civil military dictatorship (1973-1980): the school experience in authoritarian context - Perez Navarro, Camila; Zurita, Felipe (Historia y Memoria de la Educación, 2021)
This paper presents the results of an investigation that aimed to describe and analyse the transformations in the educational experience of students and teachers based on the new regulations designed and implemented by the civil-military dictatorship in Chile between 1973 and 1980. Specifically, it deals with the initiatives that sought to control and monitor various actors in the educational system at different levels and to transform relevant aspects of school culture and reorient pedagogical practices in the school. In methodological terms, various primary documentary sources were analysed, such as circulars, official letters and decree-laws published by the Ministry of Education, newspapers, and magazines. We conclude that these actions were aimed at intervening educational establishments in three main areas: in daily school life, through the incorporation and intensification of new civic and religious rites; in the purification and ideologization of educational plans and programs, and in pedagogical practices, through a hierarchical approach to the relationship between teachers and students.